PENGARUH WAKTU POLIMERISASI PADA PROSES PEMBUATAN POLIESTER DARI ASAM LEMAK SAWIT DISTILAT (ALSD) - Ahmad Rozi Tanjung, Ida Ayuningrum, Renita Manurung (Jurnal Teknik Kimia USU, 2013)
Palm Fatty Acid Distillate (PFAD) can be used as raw material for synthesis polyester. The aim of this research is to synthesis of polyester and to determine the effect of reaction time on  polymerization methyl ester PFAD. The esterification stage was done at temperature 70oC, reactiontime 120 minute, reactant ratio 1:8 (PFAD:methanol), concentration of catalyst (H2SO4) 1% (w/w) PFAD;polymerization stage was done at temperature 126-132°C, concentration ofcatalyst (BF3-diethyl etherate) 9.2 % (w/w), variation of polymerization reaction time3, 4, and 5 hours; and polyesterification stage was done at temperature 175-200 oC,reactant ratios (w/w) 1:1 (polymerized ME : ethylene glycol), reaction time 4 hours and all ofstage was stirred at 150 rpm. The results showed, in the esterification stage wasobtained methyl ester with iodine value 77.29 g I2/100 g, viscosity 6.90 cP,density 859.91 kg/m3 and analysis byusing GC-MS showed that the purity of methyl ester was 82.23% andmolecular weight 267.97 g/mol. Decreasing in iodine value from 77.294 I2 g/100 g to 63.45-61.14 gI2/100 g indicated that the polymerization process had takenplace. In polyesterification stage wasobtained gel polyester, viscous, dark brown colored solid at room temperature with acid value from13.13 to 21.65 mg KOH/g, viscosity from 14.3 to 19.1 P, and molecular weight 995.03 to 1,522.07g/mol which is more suitable for application of modified polyester. Analysis by using GC showed that the purity of polyester is equal to 65.49%.